2017
DOI: 10.14740/cr605w
|View full text |Cite
|
Sign up to set email alerts
|

B-Type Natriuretic Peptide: A Predictor for Mortality, Intensive Care Unit Length of Stay, and Hospital Length of Stay in Patients With Resolving Sepsis

Abstract: BackgroundB-type natriuretic peptide (BNP) is a hormone secreted by cardiomyocytes in response to myocardial ischemia, increased ventricular wall tension, and overload. BNP is utilized as a diagnostic and prognostic marker in congested heart failure (CHF). Its prognostic value in sepsis is unknown. The aim of this study is to determine if BNP correlates with increased in-hospital mortality for septic patients.MethodsThis was a retrospective study of 505 patients admitted for sepsis or severe sepsis or septic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Of the 46 studies included in this review, 35 examined the association of brain natriuretic peptides (BNP, NT‐proBNP) with survival in patients with septic shock, presented in Table . The vast majority were prospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 46 studies included in this review, 35 examined the association of brain natriuretic peptides (BNP, NT‐proBNP) with survival in patients with septic shock, presented in Table . The vast majority were prospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…This association was also evaluated by two studies in the setting of an RCT evaluating the use of 20% human albumin plus crystalloids or crystalloids alone in patients with severe sepsis or septic shock . In total, 30 studies, including the two conducted in the setting of the RCT, have found a significant association between elevated levels of brain natriuretic peptides and increased mortality …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations